Non‐Classical Conversion of Methanol to Formaldehyde. Issue 11 (1st September 2022) - Deitermann, Michel; Huang, Zjian; Lechler, Sebastian; Merko, Mariia; Muhler, Martin
Abstract: Non‐classical alternatives to the silver contact and the Formox processes comprise the thermal non‐oxidative dehydrogenation of methanol, for which new catalysts are needed to achieve high formaldehyde selectivity at high conversion at temperatures below 600 °C. The electro‐ or photocatalytic conversion of methanol to formaldehyde is not applied either industrially but is attractive because of mild reaction conditions and high formaldehyde selectivities. Novel gas‐phase approaches yielding (anhydrous) formaldehyde are presented describing lab‐scale setups and the challenges for up‐scaling. Abstract : The production of formaldehyde by non‐oxidative thermal dehydrogenation, electro‐ and photochemical conversion of methanol is reviewed to demonstrate the high potential of these three alternative routes to the industrially applied selective oxidation of methanol. The used catalysts, the influence of the reaction conditions, reaction mechanisms, and pros and cons are discussed, and concepts of applied laboratory setups including examples for the three routes are presented.